Cover Picture: Interfacial Architectures Derived by Lithium Difluoro(bisoxalato) Phosphate for Lithium‐Rich Cathodes with Superior Cycling Stability and Rate Capability (ChemElectroChem 1/2017). Issue 1 (15th December 2016) - Han, Jung‐Gu; Park, Inbok; Cha, Jiho; Park, Suhyeon; Park, Sewon; Myeong, Seungjun; Cho, Woograe; Kim, Sung‐Soo; Hong, Sung You; Cho, Jaephil; Choi, Nam‐Soon
Abstract : The Front Cover picture illustrates the lithium difluoro(bisoxalato)phosphate (LiDFBP)‐derived solid electrolyte interphase layer effectively suppressing unwanted electrolyte decomposition at high voltages and mitigating the voltage decay of lithium‐rich cathodes caused by phase transformation to spinel‐like phases during cycling. More information can be found in the Article by N.‐S. Choi and co‐workers onpage 56 in Issue 1, 2017 (DOI:10.1002/celc.201600297 ).